2009
DOI: 10.1097/inf.0b013e31819588ac
|View full text |Cite
|
Sign up to set email alerts
|

Management of Newborn Infections in Primary Care Settings

Abstract: Although methodological limitations preclude estimating the precise contribution of antibiotics toward neonatal mortality reduction in community settings in low income countries, available data suggest substantial benefit of case management approaches using antibiotics for neonatal sepsis in such settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 31 publications
1
18
0
1
Order By: Relevance
“…However, two studies evaluating community-based neonatal care packages including injectable antibiotics found 44% and 34% reductions in neonatal mortality (RR 0.56, 95% CI 0.41,0.77; RR 0.66, 95% CI 0.47, 0.93 respectively), but the interpretation of these results is complicated by co-interventions [75]. Similar findings were reported by Bhutta et al in a review on community-based management of neonatal sepsis; the review reported 27% reduction in all-cause neonatal mortality (95% CI: 18, 35%), and 42% reduction in pneumonia specific mortality (95% CI: 22,57%) [76]. On the basis of available evidence it can be concluded that antibiotics have a clear role in reducing neonatal mortality in LMICs and can be effectively administered at homes via trained health workers as well as for hospital-based management of neonatal sepsis.…”
Section: Methodssupporting
confidence: 58%
“…However, two studies evaluating community-based neonatal care packages including injectable antibiotics found 44% and 34% reductions in neonatal mortality (RR 0.56, 95% CI 0.41,0.77; RR 0.66, 95% CI 0.47, 0.93 respectively), but the interpretation of these results is complicated by co-interventions [75]. Similar findings were reported by Bhutta et al in a review on community-based management of neonatal sepsis; the review reported 27% reduction in all-cause neonatal mortality (95% CI: 18, 35%), and 42% reduction in pneumonia specific mortality (95% CI: 22,57%) [76]. On the basis of available evidence it can be concluded that antibiotics have a clear role in reducing neonatal mortality in LMICs and can be effectively administered at homes via trained health workers as well as for hospital-based management of neonatal sepsis.…”
Section: Methodssupporting
confidence: 58%
“…In cases of pneumonia in older children (6–59 months), the dose was 5 mL/day for 5 days (250 mg of SMX/day). No untoward effects, including any signs of central nervous system (CNS) toxicity, were mentioned in these reports (Bang et al, 1999, 2005; Bhutta et al, 2009). However, these reports do not confirm the presence or existence of any toxicity.…”
Section: Resultsmentioning
confidence: 95%
“…It is used orally in conjunction with gentamycin (injectable), the latter being effective mostly against Gram-negative organisms and the Gram-positive Staphylococcus . In neonates (≥2500 g body weight) diagnosed with sepsis or pneumonia, the course of an oral dose of Cotrimoxazole syrup (200 mg of SMX plus 40 mg of TMP in 4 mL) was 1.25 mL twice a day for 7 days (Bang et al, 1999, 2005; Bhutta et al, 2009). Therefore, each neonate received 125 mg of SMX per day.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations